Diastolic Plateau – Invasive Hemodynamic Marker of Adverse Outcome Among Left Ventricular Assist Device Patients - Grupper, Avishay; Kodesh, Afek; Lavee, Jacob; Fefer, Paul; Barbash, Israel M.; Elian, Dan; Kogan, Alexander; Morgan, Avi; Segev, Amit; Maor, Elad (Frontiers in Cardiovascular Medicine, 2022)
Background Diastolic plateau is an invasive hemodynamic marker of impaired right ventricular (RV) diastolic filling. The purpose of the current analysis was to evaluate the prognostic importance of this sign in left ventricular assist device (LVAD) patients. Methods The analysis included all LVAD patients who received continuous-flow LVAD (HeartMate 3) at the Sheba medical center and underwent right heart catheterization (RHC) during follow up post-LVAD surgery. Patients were dichotomized into 2 mutually exclusive groups based on a plateau duration cutoff of 55% of diastole. The primary end point of the current analysis was the composite of death, heart transplantation, or increase in diuretic dosage in a 12-month follow-up period post-RHC. Results Study cohort included 59 LVAD patients with a mean age of 57 (IQR 54–66) of whom 48 (81%) were males. RHC was performed at 303 ± 36 days after LVAD surgery. Patients with and without diastolic plateau had similar clinical, echocardiographic, and hemodynamic parameters. Kaplan–Meier survival analysis showed that the cumulative probability of event at 1 year was 65 ± 49% vs. 21 ± 42% for primary outcomes among patients with and without diastolic plateau (p Log rank < 0.05 for both). A multivariate model with adjustment for age, INTERMACS score and ischemic cardiomyopathy consistently showed that patients with diastolic plateau were 4 times more likely to meet the study composite end point (HR = 4.35, 95% CI 1.75–10.83, p = 0.002). Conclusion Diastolic plateau during RHC is a marker of adverse outcome among LVAD patients.